Searching for Workers’ Solidarity: The One Big Union and the Victoria General Strike of 1919 - Isitt, Benjamin (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2007)
Abstract On 23 June 1919, 5000 workers affiliated with Victoria’s Metal Trades Council downed tools in sympathy with Winnipeg workers and as a protest against what they called ‘Star Chamber’ methods of repression against the working class leadership. While much has been written on the Winnipeg General Strike and 1919 Canadian labour revolt, the Victoria General Strike is revealing as a contested expression of working-class solidarity, an illustration of the unresolved tension between craft and industrial unionism and different labour leaderships in the west-coast city. Much of British Columbia labour had embraced the One Big Union and its socialist leadership by the spring of 1919, but Victoria’s organized workers wavered on the question of striking in sympathy with Winnipeg’s working class. While the shipyards were a locus of militancy, influential groups of workers, afl rather than obu in orientation, opposed a general strike and undermined the mood of solidarity. Local conditions in different economic sectors shaped the working-class response to the Winnipeg General Strike. This tension provides fresh insight into the development of class consciousness and industrial militancy at the end World War I, breaking new ground in the historiography of Canada’s postwar labour revolt.